Кадрове забезпечення галузі туризму з урахуванням міжнародного досвіду - Бунтова, Н.В. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье изложены проблемы кадрового обеспечения в туризме и гостиничном хозяйстве Украины с учетом международного опыта. Определены наиболее актуальные вопросы управления персоналом гостиничных и туристических предприятий. Разработана система мероприятий и научно-практических рекомендаций по усовершенствованию механизма кадрового обеспечения на макро- и мезоуровне. In this article there are the problems of personnel maintenance in tourism and hotel facilities of Ukraine taking into account the international experience. The main questions of staff control of the hotels and tourist firms are determined. The system of measures and scientific-practical guidelines on personnel maintenance improvement on macrolevel and middlelevel is developed.